2010
DOI: 10.2147/ijn.s5238
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of human astrocytoma U87 cells with silicon dioxide nanoparticles lowers their survival and alters their expression of mitochondrial and cell signaling proteins

Abstract: Recent evidence suggests silicon dioxide micro- and nanoparticles induce cytotoxic effects on lung cells. Thus, there is an increasing concern regarding their potential health hazard. Nevertheless, the putative toxicity of nanoparticles in mammalian cells has not yet been systematically investigated. We previously noted that several metallic oxide nanoparticles exert differential cytotoxic effects on human neural and nonneural cells. Therefore, we hypothesized that silicon dioxide nanoparticles induce cytotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 23 publications
(49 reference statements)
2
14
0
Order By: Relevance
“…In addition, the treatment had negative effects on the NGF-induced differentiation where number of neurites/cell, neurite length, and intercellular contacts/cell all decreased as a function of dose. A similar effect on survival was seen in the work by Lai et al [ 79 ] where U87 astrocytoma cells were exposed for 48 h to 12 nm SiO 2 NP. A dose-dependent decrease in cell survival was seen at ≥ 25µg/ml, accompanied by an increased activity of two mitochondrial enzymes and decreased levels of certain mitochondrial proteins and decreased ERK signaling.…”
Section: Effects On the Nervous Systemsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, the treatment had negative effects on the NGF-induced differentiation where number of neurites/cell, neurite length, and intercellular contacts/cell all decreased as a function of dose. A similar effect on survival was seen in the work by Lai et al [ 79 ] where U87 astrocytoma cells were exposed for 48 h to 12 nm SiO 2 NP. A dose-dependent decrease in cell survival was seen at ≥ 25µg/ml, accompanied by an increased activity of two mitochondrial enzymes and decreased levels of certain mitochondrial proteins and decreased ERK signaling.…”
Section: Effects On the Nervous Systemsupporting
confidence: 82%
“…Both Wang et al [ 78 ] and Lai et al [ 79 ] investigated effects of SiO 2 NPs on cell survival and other end-points in two human cell lines with origin in the nervous system. The work by Wang et al employed NGF-treated PC12 cells that were subjected to 20 and 50 nm SiO 2 NPs for 12-48 h. The treatment caused a concentration and time-dependent decrease in cell survival which seemed to be mediated by increased oxidative stress.…”
Section: Effects On the Nervous Systemmentioning
confidence: 99%
“…Various reports have indicated that U87 human glioblastoma cells may be used as astrocytes for AD neuropathology and cytotoxicity studies ( 19 21 ). As a cellular marker of astrocytes, GFAP (green staining) was highly expressed on U87 cells that were not treated with Aβ 1–42 (0 µM group; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the surface properties of the nanocarriers can be modified for a selective, controlled drug release with minimal side effects and increased efficacy [ 84 , 94 , 95 ]. Nanomaterial based chemotherapeutic agents such as the liposomes, dendrimers, or polymeric micelles are reported to circumvent the BBB and reach the target site of action [ 87 , 88 , 96 , 97 ]. Several nanomaterials-based drugs have been evaluated for the treatment of GBM and other cancers.…”
Section: New Approaches To Drug Deliverymentioning
confidence: 99%